2009
DOI: 10.1016/j.jep.2009.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Berberine and Coptidis Rhizoma as novel antineoplastic agents: A review of traditional use and biomedical investigations

Abstract: The modern evidences of treating cancer with huanglian and berberine have a strong linkage with traditional concept and rules of using huanglian in CM practice. As anticancer candidates with low toxicity, berberine and its altered structure, as well as huanglian and its formulae, will attract scientists to pursue the potential anticancer effects and the mechanisms by using technologies of genomics, proteomics and other advanced approaches. On the other hand, relatively few in vivo studies have been conducted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
308
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 447 publications
(314 citation statements)
references
References 82 publications
4
308
0
2
Order By: Relevance
“…Recent studies have revealed that berberine suppresses the growth of some tumor cell lines (Letasiova et al, 2006;Jantova et al, 2007;Liang et al, 2008;Tang et al, 2009). Several studies have attempted to elucidate the mechanism of antitumor activity of berberine (Iizuka et al, 2000;Lin et al, 2004;Lee et al, 2006;Tan et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed that berberine suppresses the growth of some tumor cell lines (Letasiova et al, 2006;Jantova et al, 2007;Liang et al, 2008;Tang et al, 2009). Several studies have attempted to elucidate the mechanism of antitumor activity of berberine (Iizuka et al, 2000;Lin et al, 2004;Lee et al, 2006;Tan et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, extensive attention has been drawn to some major compounds of ZJW with regard to the anticancer effects (Tang et al 2009;Jantova et al 2007;Kang et al 2005;Pan et al 2012). Our previous studies (Wang et al 2008;Wang et al 2009) have shown that berberine and evodiamine have synergistic inhibitory effects on SMMGC-7721 cells, and ZJW is more powerful than C. Chinese Frach and E. rutaecarpa (Juss.)…”
Section: Introductionmentioning
confidence: 99%
“…ber of reports, Coptis japonica Makino and its components, berberine, have been used to control airway allergic or infl ammatory diseases and reported to have anti-infl ammatory and anti-cancer effects (Yoo et al, 2008;Sun et al, 2009;Tang et al, 2009). On the other hand, it was previously reported that berberine stimulated basal mucin release from airway goblet cells, by our group .…”
Section: Introductionmentioning
confidence: 81%